The undrowned child - Lovric, Michelle (Delacorte Press, 2011)
In 1899, eleven-year-old Teodora goes with her scientist parents from Naples to Venice, Italy, which is falling victim to a series of violent natural disasters, and once there she is drawn into a web of mysterious adventures involving mermaids, an ancient prophecy, and the possible destruction of the city itself.